The Relationship of Nutrition Literacy, Eating Pattern, and Nutritional Status among Medical Students - Theresia Widyakirana Noviandewi; Prissilia Nanny Djaya (Journal of Urban Health Research, 2023)
Introduction: Nutrition literacy is the ability to search, obtain, understand, and apply nutrition information. Low nutrition literacy may cause a negative impact in eating patterns and nutritional status. This study aims to determine the relationship between nutrition literacy with eating pattern and nutritional status among medical students in the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia. Methods: This study was a descriptive analytic cross-sectional study among 97 medical students of the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia. Nutrition literacy was measured with The Newest Vital Sign questionnaire. Food consumption data was collected with the 24-hours recall questionnaire. Nutritional status was measured based on body mass index (BMI). Research data were analyzed using the Rank Spearman test. Results: Based on the data analysis, there were 66% of students with adequate nutrition literacy, 66,3% of students with improper diet, and 44,3% of students with normal nutritional status. The bivariate result showed that there was no association between nutrition literacy with nutritional status (P = 0,057), nutrition literacy and eating pattern for carbohydrates (P = 0,562), protein (P = 0,876), and fat (P = 0,569).Conclusions: There was no association between nutrition literacy with eating pattern and nutritional status among medical students in the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia.